Allylpyrocatechol, isolated from betel leaf ameliorates thyrotoxicosis in rats by altering thyroid peroxidase and thyrotropin receptors - Sunanda Panda (Nature Portfolio, 2019)
Abstract Allylpyrocatechol (APC) was isolated from betel leaf and its possible role in L-thyroxin (L-T4)-induced thyrotoxic rats was evaluated. The disease condition, thyrotoxicosis was confirmed by higher levels of thyroid hormones and low thyrotropin (TSH) in serum. Increased hepatic activities of 5′-mono-deiodinase(5′D1), glucose-6-phospatase (G-6-Pase); serum concentrations of alanine transaminase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase(LDH) and tumour necrosis factor-alpha(TNF-α) were observed in thyrotoxic rats. Hepatic lipid peroxidation(LPO) was also increased and the endogenous antioxidants were depleted in these rats. In western blot analysis thyroid peroxidase expression was found to be reduced, whereas thyrotropin receptor(TSHR) expression was enhanced in thyroid gland of these animals. On the other hand, APC treatment in thyrotoxic rats decreased the levels of serum thyroid hormones, ALT, AST, TNF-α and LDH, as well as hepatic 5′ D1 and G-6-Pase activities. However, it increased the serum TSH levels. APC also reduced the hepatic LPO and increased the cellular antioxidants in thyrotoxic rats. However, expression of TSHR was inhibited and TPO was increased by APC. The test compound also improved histological features in both liver and thyroid. Present report appears to be the first one that indicates the positive role of APC in ameliorating T4-induced thyrotoxicosis.